Is consent to psychological interventions less important than consent to bodily interventions? - Forsberg, L; Douglas, T; Savulescu, J (Oxford University Press, 2025)
It is standardly accepted that medical interventions can be permissibly administered to a patient who has decision-making capacity only when she has given her valid consent to the intervention. However, this requirement for valid medical consent is much less frequently discussed in relation to psychological interventions (‘PIs’) than it is in relation to bodily interventions (‘BIs’). Moreover, legal and professional consent requirements in respect of PIs are laxer than the analogous requirements in respect of BIs. One possible justification for these differences appeals to the Differential Importance View—the view that it is presumptively morally less important to obtain explicitly given valid consent for PIs than for BIs. In this article we argue against the Differential Importance View by considering and rejecting three possible justifications for it. These invoke differences between PIs and BIs with respect to implicit consent, risk, and wrongfulness.